Influence of rhythmic-movement activity intervention on hot executive function of 5- to 6-year-old children - Wang, Suxia; Yang, Anning; Wei, Xuefeng; Qian, Ruohan; Chen, Ying; Bi, WenJing; Hu, Bisheng; Wen, Cheng (Frontiers in Psychology, 2024)
Hot Executive Function (hot EF) refers to cognitive process involved in high emotion or motivation, and the operation of this function is related to the activities of the ventromedial prefrontal lobe and orbitofrontal lobe. Meanwhile, rhythmic-movement activity is a musical activity in which one expresses and feels music with one’s own body movements which involves cognitive abilities such as adjusting and understanding emotions among children. To explore how rhythmic-movement activity with rewards influences the development of hot EF in children of 5–6 years old, the organization principles of rhythmic-movement activity with rewards intervention on hot EF were designed, and 62 children of 5–6 years old in a kindergarten in Yantai of China were selected as research participants (M = 5.80 years old, SD = 0.37 years old) for pre-test and post-test experimental design. The experimental group received rhythmic-movement activity with rewards three times a week for 6 weeks, while the control group did not. The gift delay task and the children’s gambling task were used to measure two sub-components of hot EF before and after the intervention, and the results show that rhythmic-movement activity with rewards has a significant effect on gratification delay and affective decision-making ability of children. Finally, the effects and enlightenment of rhythmic-movement activity with rewards on hot EF are discussed.